Using Free/Libre Open Source Software Projects as E-learning Tools - Cerone, Antonio; Sowe, Sulayman (Electronic Communications of the EASST, 2010)
Free/Libre Open Source Software (FLOSS) projects can be considered as learning environments in which heterogeneous communities get together to exchange knowledge through discussion and put it into practice through actual contributions to software development, revision and testing. This has encouraged tertiary educators to attempt the inclusion of participation in FLOSS projects as part of the requirements of Software Engineering courses, and pilot studies have been conducted to test the effectiveness of such an attempt. This paper discusses two pilot studies with reference to several studies concerning the role of learning in FLOSS projects and shows how using FLOSS projects as E-learning tools has a potential to increase the quality of the software product.